Identificação étnico-racial na voz de crianças em espaços de educação infantil - Trinidad, Cristina Teodoro (2011)
This study aimed to determine: a) if - and how - children in preschool understand racial- ethnic identification; b) the criteria they employ to do so; and c) the means by which this identification is formulated. The research was conducted in an elementary school, situated in the west part of the city of São Paulo, SP, Brazil, involving 33 children between 4 and 5 years old. The theoretical framework includes approaches to the ethnic-racial identification, specifically those that consider race as a social construction. Furthermore, some categories of the socio-historical theory in Psychology, in particular, the appropriation of 'senses and meanings' were employed. Finally, it was adopted the notion of child proposed by Sociology of Childhood, which sees children as a legitimate social actor, one who produces symbols, representations and beliefs that contribute to their own cultures. The literature review was mainly from North-America, since in Brazil, there are few studies dealing with ethnic and/or racial identification made by children or adolescents. Methodologically, an ethnographic approach was employed in this study, using the following procedures for data collection: participant observations, informal conversations, children s storytelling and document analysis. The results show that young children know and employ racial-ethnic categories while playing or interacting with their peers, but do not select their friends based on their skin color. Nevertheless, they do verbalize a desire to have characteristics not associated with blacks, hair and skin tone being those most frequently mentioned. Apparently, all this indicates that meanings socially constructed, for both whites and blacks, have been appropriate by those children, being especially difficult to handle for those of interracial relationships. In fact, as the similarity to black people increases, the desire of being white intensifies. Finally, it is important to mention that the male and female roles have also been duly appropriated and are reproduced by girls and boy in their everyday life. This situation reveals the urgency of breaking the tendency to reproduce and perpetuate gender discriminations present in society. Lastly, the e results show that adults working at the elementary school as well as the children's own parents do not consider that to answer questions regarding color or race can be of any use, demonstrating a lack of knowledge about the importance of educating children to recognize ethnic and racial diversity as something to be respected and positively valued